Gustiness and temperature at Nagpur - SHARMA, KK (MAUSAM, 1967)
Ten years autographic records of wind and temperature have been utilised for the present study. The seasonal and diurnal variations of mean wind speed, average range of gusts and gustiness along with the temperature variations have been worked out.